THE IMPLEMENTATION OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE TO INCREASE GRADE 8 STUDENTS’ ACTIVE LEARNING IN AN ENGLISH CLASS - Carollina Anggi Puspitasari; Dylmoon Hidayat (Polyglot, 2018)
Based on class observations, some students in grade 8 of XYZ Junior High School were not contributing actively in an English class. One of the reason was because they were not used to speaking English. This research was aimed at increasing students’ active learning in studying English in the classroom by implementing the Cooperative Integrated Reading Composition (CIRC) technique. The research method used was Classroom Action Research (CAR) of Kemmis and McTaggart’s, conducted within three cycles. The subjects were four students who were not speaking English actively. The data was collected through questionnaires and mentor’s observation checklist. The result showed that the implementation of the CIRC technique in an English class could increase students’ active learning significantly.BAHASA INDONESIA ABSTRAK: Berdasarkan hasil observasi di VIII SMP XYZ tidak berpartisi aktif saat pembelajaran Bahasa Inggris. Salah satu alasannya adalah siswa tidak terbiasa menggunakan bahasa Inggris. Tujuan dari penelitian ini adalah meningkatkan keaktifan siswa kelas VIII SMP dalam pembelajaran Bahasa Inggris dengan menggunakan teknik Cooperative Integrated Reading Composition (CIRC). Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart dengan 3 siklus. Subyek penelitian berfokus pada empat orang siswa yang tidak terlibat secara aktif di kelas Bahasa Inggris. Data dikumpulkan dengan kuesioner dan checklist observasi mentor. Hasil penelitian memperlihatkan bahwa dengan penerapan teknik CIRC dalam kelas Bahasa Inggris, keaktifan siswa mengalami kenaikan yang signifikan.